Biogastronomy: Factors that determine the biological response to meal ingestion. Issue 7 (2nd February 2018) - Pribic, T.; Azpiroz, F.
Abstract: Background: The biological response to a meal includes physiological changes, primarily related to the digestive process, and a sensory experience, involving sensations related to the homeostatic control of food consumption, eg, satiety and fullness, with a hedonic dimension, ie associated with changes in digestive well‐being and mood. The responses to a meal include a series of events before, during and after ingestion. While much attention has been paid to the events before and during ingestion, relatively little is known about the postprandial sensations, which are key to the gastronomical experience. Purpose: The aim of this narrative review is to provide a comprehensive overview and to define the framework to investigate the factors that determine the postprandial experience. Based on a series of proof‐of‐concept studies and related information, we propose that the biological responses to a meal depend on the characteristics of the meal, primarily its palatability and composition, and the responsiveness of the guest, which may be influenced by multiple previous and concurrent conditioning factors. This information provides the scientific backbone to the development of personalized gastronomy. Abstract : Factors that determine the postprandial experience. The biological response to meal ingestion involves physiological changes, eg, the digestive process, and a sensory experience including homeostatic sensations (satiety, fullness) with a hedonic dimension (digestive well‐being, mood), ie, the postprandial experience. The normal postprandial experience depends on the characteristics of the meal and the responsiveness of the eater, which may be influenced by multiple previous and concurrent conditioning factors.